The relationship between quality of sleep and night shift rotation interval. Issue 1 (December 2015) - Kim, Jae; Chae, Chang; Kim, Young; Son, Jun; Kim, Ja; Kim, Chan; Park, Hyoung; Lee, Jun; Kwon, Soon
Abstract Background Shift work is closely related with workers' health. In particular, sleep is thought to be affected by shift work. In addition, shift work has been reported to be associated with the type or direction of shift rotation, number of consecutive night shifts, and number of off-duty days. We aimed to analyze the association between the night shift rotation interval and the quality of sleep reported by Korean female shift workers. Methods In total, 2, 818 female shift workers from the manufacturing industry who received an employee physical examination at a single university hospital from January to August in 2014 were included. Subjects were classified into three groups (A, B, and C) by their night shift rotation interval. The quality of sleep was measured using the Korean version of the Pittsburgh Sleep Quality Index (PSQI). Descriptive analysis, univariate logistic regression, and multivariate logistic regression were performed. Results With group A as the reference, the odds ratio (OR) for having a seriously low quality of sleep was 1.456 (95% CI 1.171–1.811) and 2.348 (95% CI 1.852–2.977) for groups B and C, respectively. Thus, group C with the shortest night shift rotation interval was most likely to have a low quality of sleep. After adjustment for age, obesity, smoking status, alcohol consumption, exercise, being allowed to sleep during night shifts, work experience, and shift work experience, groups B and C had ORs of 1.419 (95% CI 1.134–1.777) and 2.238 (95% CI 1.737–2.882), respectively, compared to group A. Conclusion Our data suggest that a shorter night shift rotation interval does not provide enough recovery time to adjust the circadian rhythm, resulting in a low quality of sleep. Because shift work is influenced by many different factors, future studies should aim to determine the most optimal shift work model and collect accurate, prospective data.